The contemporary world : looking through the lenses of globalization - Bihasa, Carmelo Rico S. (Mandaluyong City : Books Atbp. Publishing Corp., 2022)
"This book provides a unique and interesting introduction to the concept of globalization. It provides the students-who are engaged in the study of the contemporary world-with a sound and logical approach in analyzing and understanding the complex nature of globalization. This book proceeds with the assumption that globalization exhibits a multi-dimensional character that takes on the study of the concept through a number of critical dimensions. This book likewise assumes that the globalization that occurred several years ago is not the same phenomenon that the members of the international community are facing at the moment."
Includes references and index.
English.
Keywords: Globalization